Identification of Bipotential Blood Cell/Nephrocyte Progenitors in Drosophila: Another Route for Generating Blood Progenitors - Morin-Poulard, Ismaël; Destalminil-Letourneau, Manon; Bataillé, Laetitia; Frendo, Jean-Louis; Lebreton, Gaëlle; Vanzo, Nathalie; Crozatier, Michèle (Frontiers in Cell and Developmental Biology, 2022)
The Drosophila lymph gland is the larval hematopoietic organ and is aligned along the anterior part of the cardiovascular system, composed of cardiac cells, that form the cardiac tube and its associated pericardial cells or nephrocytes. By the end of embryogenesis the lymph gland is composed of a single pair of lobes. Two additional pairs of posterior lobes develop during larval development to contribute to the mature lymph gland. In this study we describe the ontogeny of lymph gland posterior lobes during larval development and identify the genetic basis of the process. By lineage tracing we show here that each posterior lobe originates from three embryonic pericardial cells, thus establishing a bivalent blood cell/nephrocyte potential for a subset of embryonic pericardial cells. The posterior lobes of L3 larvae posterior lobes are composed of heterogeneous blood progenitors and their diversity is progressively built during larval development. We further establish that in larvae, homeotic genes and the transcription factor Klf15 regulate the choice between blood cell and nephrocyte fates. Our data underline the sequential production of blood cell progenitors during larval development.